105 Palliative care needs of adults with neuromuscular disorders: a pilot clinic. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Macfarlane, Mike; Willis, Tracey; Willis, Derek
Abstract : Background: Neuromuscular disorders (NMD) have traditionally been managed by paediatric services. As more patients with these conditions are now living into adulthood, however, it is unclear a) what the palliative care needs are for this new adult population and b) how palliative care services can meet these needs. Methods: A 12 month pilot clinic was run jointly by a palliative medicine consultant and members of the neuromuscular multidisciplinary team (MDT) from a regional NMD centre. The aim of the clinic was to assess a) the number of patients, b) diagnoses and c) symptom burden that required palliative care input. Patients were recruited if the NMD MDT assessed that they had significant symptom burden or that their disease trajectory had changed. Results: 9 patients were recruited to the joint clinic which was conducted 4 times in the year. These patients had a range of neuromuscular conditions and a variety of symptoms. Pain was the most commonly encountered symptom and ranged from very mild to severe with a mean pain score at initial assessment of 3 out of 5 (moderate). Conclusions: Adult patients with a variety of neuromuscular disorders were identified as having an unmet palliative care need. A range of symptoms were identified, with moderate pain being the most common. Despite these patients' symptom burden they are seldom referred to palliative care services.